Fodor's American Southwest. - Fodor's Travel Publications, Inc. (New York : Fodor's Travel Publications, 2009)
A comprehensive travel guide to the American Southwest, with maps and information on hotels and restaurants, shopping and entertainment, and other interesting sites.
Includes index.
Map on endpaper.
Young Adult
Keywords: Southwestern States -- Guidebooks; Southwestern States -- Description and travel; Southwestern States -- Guidebooks; Southwestern States -- Description and travel